"Wenn eine Maus in den Brunnen fällt ..." Rezeptionsgeschichtliche Anmerkungen zu ἀκαθαρσία unter bes. Berücksichtigung der byzantinischen Rechtsgeschichte - Synek, Eva Maria (Protokolle zur Bibel, 2012)
Neither in East nor West did the fact that various texts from the New Testament stress an ethical meaning of purity hinder the continuation of a more traditional conception of purity. The focus of this article on different Christian receptions of “akatharsia” is on byzantine legal history. It mainly deals with food taboos, but also with the cultic dimension of celibacy and other related topics such as menstruation and child-birth.